Subglacial plumes - Hewitt, I (Annual Reviews, 2019)
Buoyant plumes form when glacial ice melts directly into the ocean or when subglacial meltwater is discharged to the ocean at depth. They play a key role in regulating heat transport from the ocean to the ice front, and in exporting glacial meltwater to the open ocean. This review summarizes current understanding of the dynamics of these plumes, focusing on theoretical developments and their predictions for submarine melt rates. These predictions are sensitive to ocean temperature, the magnitude and spatial distribution of subglacial discharge, the ambient stratification, and, in the case of sub–ice shelf plumes, the geometry of the ice shelf. However, current understanding relies heavily on parameterizations of melting and entrainment, for which there is little in the way of validation. New observational and experimental constraints are needed to elucidate the structure of the plumes and lend greater confidence to the models.